Biosensor-driven adaptive laboratory evolution and modular pathway engineering for high-level production of nicotinamide mononucleotide in yeast - Ruirui Shi; Qiancheng Han; Yingxue Xu; Lei Li; Fuping Lu; Yixun Jiang; Zhengqiang Jiang; Hui-Min Qin (Bioresource Technology, 2026)

1,12-cyclic-apelin-12 counters vascular smooth muscle cell proliferation and atherosclerosis through inhibiting aerobic glycolysis - Ruirui Lu; Xiaosi Zhou; Huimei Liu; Sisi Fan; Xiaohui Huang; Fengting Guo; Bin Huang; Linxi Chen; Lanfang Li (Toxicology and Applied Pharmacology, 2026)

Novel mutation sites in yeast FAS enhance the production of C6–C10 fatty acids and their ethyl esters - Yupeng Wang; Junbao Gong; Xinyu Lu; Yanfang Chen; Ruirui Li; Ying Guo; Chunhong Sun; Xinjian Wang; Ying Zhou; Xiaole Wu; Yefu Chen (Food Bioscience, 2026)

Bioactive earthworm proteins and peptides from traditional Chinese medicine: structural diversity, biomedical applications, and emerging biomanufacturing strategies - Hanzhi Weng; Fengling Yang; Zhiliang Hou; Siyan Zhou; Jie Lu; Xiaoyuan Sun; Ruirui Xu; Zhen Kang (Systems Microbiology and Biomanufacturing, 2026)

Scalable ergothioneine production via integrating chemical methylation and rhodanese-catalyzed CS bond formation - Jie Lu; Xiaoyuan Sun; Hanzhi Weng; Weiquan Ding; Fengling Yang; Guochen Du; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2026)

Cuproptosis and Its Impact on Cardiovascular Health: Mechanisms and Therapeutic Opportunities - Xiaohui Huang; Liwen Wang; Huimei Liu; Ruirui Lu; Lanfang Li (Cardiovascular Toxicology, 2026)

PtRu synergistic effect facilitates hydrogenation of liquid organic hydrogen carrier in aqueous phase under ambient pressure - Shuhan Lu; Jiao He; He Jiang; Yixiao Wang; Ruirui Hu; Xiang Gong; Bin Wang; Chunhai Yi; Fusheng Yang; Tao Fang (Chemical Engineering Journal, 2026)

Bimetallic chloride in situ etching of NiFe alloy substrate to synthesize porous coral structure catalyst for efficient oxygen evolution reaction - Yu Zhang; Yaoxia Yang; Biaobiao Lu; RuiRui Zhang; Fuxing Zhou; Dongfei Sun; Qingtao Wang; Jian Li; Ziqiang Lei (Fuel, 2025)

A multi-sensor, phenology-based approach framework for mapping cassava cultivation dynamics and intercropping in highly fragmented agricultural landscapes - Xincheng Wang; Qinfei Wang; Hongyan Lai; Zhenwen Zhang; Ting Yun; Xiaojing Lu; Guizhen Wang; Shangye Lao; Qi Liao; Saiqing Lu; Ruirui Chen; Shijing Fang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Large electrocaloric temperature change in lead-free (Bi0.47Na0.47Ba0.06)TiO3-based ceramics via regulating non-ergodic - ergodic transition - Junwen Mei; Mei Bai; Yangfei Gao; Ruirui Kang; Xiangran Pei; Haichao Hu; Junjie Xiong; Jiantuo Zhao; Feng Li; Dezhen Xue; Zhongliang Lu; Xiaojie Lou (Chemical Engineering Journal, 2025)

Impact of micro- and nano-plastics on marine organisms under environmentally relevant conditions - Ruirui Wang; Hongmei Tan; Xiaochen Huang; Jianjun Wang; Wenli Su; Farhana Maqbool; Lu Liu; Yuanshuo Ma; Meng Wang; Zhuomiao Liu; Xia Liu; Yanhui Dai; et al. (Aquatic Toxicology, 2025)

Establishment of reference intervals for serum immunoglobulin G N-glycosylation features in healthy Chinese adults: a nationwide survey in the framework of predictive, preventive, and personalized medicine - Changyu Liu; Yinghao Wang; Xingang Li; Xiaojia Xu; Ruirui Xu; Cuihong Tian; Zhixian Chen; Xinxia Lu; Yuejin Li; Meng Wang; Zhaoyang Tang; Xueyu Chen; et al. (EPMA Journal, 2025)

Antifungal immunity: advances in PRR recognition, adaptive responses, and immune-based therapies - Jianlin Zhou; Xueni Lu; Ruirui He; Yanyun Du; Bo Zeng; Lingyun Feng; Ming Yi; Yuan Wang; Chenhui Wang (Science China Life Sciences, 2025)

RAP1 is essential for PRRSV replication and the synthesis of the viral genome - Qiumei Wang; Heyou Yi; Anli Chen; Tao Tian; Zhiqing Yu; Lechen Lu; Ruirui Ye; Ermin Xie; Guoxin Zheng; Guihong Zhang; Heng Wang (Veterinary Microbiology, 2025)

Genomic comparison of male and female spotted seals in the Liaodong Gulf, China - Shengyong Xu; Xiaoyan Xie; Ruirui Zhao; Jiashen Tian; Zhichuang Lu (Regional Studies in Marine Science, 2024)

Perfluoroalkyl substances exposure and the risk of breast cancer: A nested case-control study in Jinchang Cohort - Qian Dou; Yana Bai; Yongjun Li; Shan Zheng; Minzhen Wang; Zhongge Wang; Jianyun Sun; Desheng Zhang; Chun Yin; Li Ma; Yongbin Lu; Lizhen Zhang; et al. (Environmental Research, 2024)

Grape Seed Proanthocyanidins Protect Pancreatic β Cells Against Ferroptosis via the Nrf2 Pathway in Type 2 Diabetes - Haiyan Li; Haowei Zhang; Tongling Wang; Liyuan Zhang; Hao Wang; Heng Lu; Ruirui Yang; Yusong Ding (Biological Trace Element Research, 2024)
Pancreatic β cell damage is the primary contributor to type 2 diabetes mellitus (T2DM); however, the underlying mechanism remains nebulous. This study explored the role of ferroptosis in pancreatic β cell damage and the protective effects of grape seed proanthocyanidin extract (GSPE). In T2DM model rats, the blood glucose, water intake, urine volume, HbA1c, and homeostasis model assessment-insulin resistance were significantly increased, while the body weight and the insulin level were significantly decreased, indicating the successful establishment of the T2DM model. MIN6 mouse insulinoma β cells were cultured in high glucose and sodium palmitate conditions to obtain a glycolipid damage model, which was administered with GSPE, ferrostatin-1 (Fer-1), or nuclear factor erythroid 2-related factor 2 (Nrf2) small interfering (si) RNA. GSPE and Fer-1 treatment significantly improved pancreatic β-cell dysfunction and protected against cell death. Both treatments increased the superoxide dismutase and glutathione activity, reduced the malondialdehyde and reactive oxygen species levels, and improved iron metabolism. Furthermore, the treatments reversed the expression of ferroptosis markers cysteine/glutamate transporter (XCT) and glutathione peroxidase 4 (GPX4) caused by glycolipid toxicity. GSPE treatments activated the expression of Nrf2 and related proteins. These effects were reversed when co-transfected with si-Nrf2. GSPE inhibits ferroptosis by activating the Nrf2 signaling pathway, thus reducing β-cell damage and dysfunction in T2DM. Therefore, GSPE is a potential treatment strategy against T2DM. Graphical Abstract

Coordination-regulated epitaxial growth for 2D/3D perovskite vertical alignment heterostructure - Guoxiang Zhao; Yuan Chen; Shan Cong; Lutao Li; Chen Wang; Xinyu Du; Ruirui Liu; Jing Lu; Yu Liu; Gaoyuan Chen; Sihan Zhang; Liya Zhang; et al. (Science Bulletin, 2024)

Multidimensional combinatorial screening for high-level production of erythritol in Yarrowia lipolytica - Lei Li; Qianqian Zhang; Ruirui Shi; Mingdong Yao; Kangming Tian; Fuping Lu; Hui-Min Qin (Bioresource Technology, 2024)

Shared xerophytic genes and their re‐use in local adaptation to aridity in the desert plant Gymnocarpos przewalskii - Ruirui Fu; Yuxiang Zhu; Ying Liu; Zhaoping Yang; Ruisen Lu; Yingxiong Qiu; Martin Lascoux; Pan Li; Jun Chen (Molecular Ecology, 2024)
In order to thrive and survive, plant species need to combine stability in the long term and rapid response to environmental challenges in the short term. The former would be reflected by parallel or convergent adaptation across species, and the latter by pronounced local adaptation among populations of the same species. In the present study, we generated a high‐quality genome and re‐sequenced 177 individuals for Gymnocarpos przewalskii , an important desert plant species from North‐West China, to detect local adaptation. We first focus on ancient adaptation to aridity at the molecular level by comparing the genomic data of 15 species that vary in their ability to withstand aridity. We found that a total of 118 genes were shared across xerophytic species but absent from non‐xerophytic species. Of the 65 found in G. przewalskii , 63 were under purifying selection and two under positive selection. We then focused on local adaptation. Up to 20% of the G. przewalskii genome showed signatures of local adaptation to aridity during population divergence. Thirteen of the selected shared xerophytic genes were reused in local adaptation after population differentiation. Hence, only about 20% of the genes shared and specific to xerophytic species and associated with adaptation to aridity were later recruited for local adaptation in G. przewalskii .

Design of a dual-mode ratiometric fluorescent probe via MOF-on-MOF strategy for Al (III) and pH detection - Ruirui Zhao; Wenjing Lu; Xiaojing Chai; Chuan Dong; Shaomin Shuang; Yujing Guo (Analytica Chimica Acta, 2024)

UV-C radiation promoted flavonoid synthesis during early healing in potato tuber wounds with the possible involvement of ABA and related transcription factor regulation - Xuejiao Zhang; Xiaoyuan Zheng; Ruirui Yang; Qihui Wang; Lu Bai; Di Gong; Ye Han; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2024)

Characterization and Phylogenetic Analysis of the Complete Mitochondrial Genome of white-spotted Bamboo Shark (Chiloscyllium plagiosum) - Dingfang Lu; Xiaowen Huang; Ruirui Zhao; Xiaoyan Xie; Shanshan Cai (Thalassas: An International Journal of Marine Sciences, 2024)

Metabolomics reveals antioxidant and antifungal functions of flavonoids in the early stage wounded potato tubers - Xiaoyuan Zheng; Xuejiao Zhang; Jinmei Zhao; Ruirui Yang; Lu Bai; Yongcai Li; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2023)

Synergistic effect of multi-phase and multi-domain structures induced high energy storage performances under low electric fields in Na0.5Bi0.5TiO3-based lead-free ceramics - Pu Mao; Yongguang Guo; Gang Lu; Qingsong Yan; Ruirui Kang; Ting Wang; Bing Xie; Zhiyong Liu; Lixue Zhang (Chemical Engineering Journal, 2023)

PCNA promotes PRRSV replication by increasing the synthesis of viral genome - Qiumei Wang; Heyou Yi; Yanchen Guo; Yankuo Sun; Zhiqing Yu; Lechen Lu; Ruirui Ye; Ermin Xie; Qianwen Wu; Yingwu Qiu; Weipeng Quan; Guihong Zhang; et al. (Veterinary Microbiology, 2023)

Facile treatment of municipal solid waste incineration fly ash by one-step microwave hydrothermal method: Hazards detoxification and tobermorite synthesis - Ruirui Yuan; Xiaohui Fan; Min Gan; Qianqian Zhao; Siping Lu; Shixian Li (Journal of Environmental Chemical Engineering, 2023)

Morphology and location of sensilla in the antennae and ovipositor of Sirex noctilio (Hymenoptera: Siricidae) - Enhua Hao; Rui Liu; Ruirui Xu; Pengfei Lu; Haili Qiao (Arthropod Structure & Development, 2023)

Identification and genetic analysis of major gene ST3GAL4 related to serum alkaline phosphatase in chicken - Hehe Tang; Yanchao Ma; Jianzeng Li; Zhenzhen Zhang; Wenting Li; Chunxia Cai; Lujie Zhang; Zhuanjian Li; Yadong Tian; Yanhua Zhang; Jinqing Ji; Lu Han; et al. (Research in Veterinary Science, 2023)

Bionic morphological design and interface-free fabrication of halfmoon microrobots with enhanced motion performance - Dong Liu; Dayin Sun; Jiaxin Zhou; Haoran Liu; Ruirui Guo; Bin Wang; Wenjun Ma; Zhenzhong Yang; Yuan Lu (Chemical Engineering Journal, 2023)

Genomic Comparison and Genetic Marker Identification of the White-Spotted Bamboo Shark Chiloscyllium plagiosum - Ruirui Zhao; Shanshan Cai; Dingfang Lu; Pengfei Li; Shengyong Xu; Yuan Li (Frontiers in Marine Science, 2022)
The white-spotted bamboo shark ( Chiloscyllium plagiosum ) is an ecologically and commercially important marine cartilaginous fish in the Indo-Western Pacific. However, the resources of this species are declining in recent years due to habitat degradation and overfishing. Studies on genomics and genetic markers can provide valuable information for sound management and conservation of C. plagiosum . In this study, genome resequencing data of a domesticated C. plagiosum individual were generated for genomic comparison between wild and domesticated samples. Based on 281.17 Gb of clean sequencing data, the genome size of the domesticated sample was estimated as 4.99 Gb, with heterozygosity of 0.51% and repeat ratio of 74.67%, which is about 1 Gb larger than that of the wild sample (3.85 Gb with a repeat ratio of 63.53%). By using a reference-based approach, we assembled a nearly 3.45 Gb genome sequence of the domesticated sample, with the scaffold N50 of 69.45 Mb. Subsequent identification of genome-wide microsatellite markers confirmed the different abundance of repeat elements in wild and domesticated C. plagiosum . Additionally, a total of 8,703,211 single-nucleotide polymorphisms (SNPs) were detected and annotated. The demographic analysis based on identified SNPs revealed a large and constant effective population size of C. plagiosum after the last population expansion (~0.3 million years ago). The genomic data and identified genetic markers in this study can provide fundamental and useful information for further comparative genomics, evolutionary biology, and conservation genetics of C. plagiosum .

Lack of efficacy of a partial adenosine A1 receptor agonist in neuropathic pain models in mice - Katharina Metzner; Tilman Gross; Annika Balzulat; Gesine Wack; Ruirui Lu; Achim Schmidtko (Purinergic Signalling, 2021)
Previous studies suggest that adenosine A 1 receptors (A 1 R) modulate the processing of pain. The aim of this study was to characterize the distribution of A 1 R in nociceptive tissues and to evaluate whether targeting A 1 R with the partial agonist capadenoson may reduce neuropathic pain in mice. The cellular distribution of A 1 R in dorsal root ganglia (DRG) and the spinal cord was analyzed using fluorescent in situ hybridization. In behavioral experiments, neuropathic pain was induced by spared nerve injury or intraperitoneal injection of paclitaxel, and tactile hypersensitivities were determined using a dynamic plantar aesthesiometer. Whole-cell patch-clamp recordings were performed to assess electrophysiological properties of dissociated DRG neurons. We found A 1 R to be expressed in populations of DRG neurons and dorsal horn neurons involved in the processing of pain. However, administration of capadenoson at established in vivo doses (0.03–1.0 mg/kg) did not alter mechanical hypersensitivity in the spared nerve injury and paclitaxel models of neuropathic pain, whereas the standard analgesic pregabalin significantly inhibited the pain behavior. Moreover, capadenoson failed to affect potassium currents in DRG neurons, in contrast to a full A 1 R agonist. Despite expression of A 1 R in nociceptive neurons, our data do not support the hypothesis that pharmacological intervention with partial A 1 R agonists might be a valuable approach for the treatment of neuropathic pain.

The participation of basolateral amygdala in the efficacy of acupuncture with deqi treating for functional dyspepsia - Ruirui Sun; Zhaoxuan He; Peihong Ma; Shuai Yin; Tao Yin; Xiaoyan Liu; Jin Lu; Yuzhu Qu; Tingting Zhang; Liuyang Huang; Xueling Suo; Du Lei; et al. (Brain Imaging and Behavior, 2021)

A simple and low-energy method to prepare loratadine nanosuspensions for oral bioavailability improvement: preparation, characterization, and in vivo evaluation - Dandan Yang; Ruirui Li; Fang Zhang; Li Qin; Feifei Peng; Shanshan Jiang; Huiyang He; Xiumei Lu; Peng Zhang (Drug Delivery and Translational Research, 2020)

Calcium carbonate precipitation by Synechocystis sp. PCC6803 at different Mg/Ca molar ratios under the laboratory condition - Zuozhen Han; Ruirui Meng; Huaxiao Yan; Hui Zhao; Mei Han; Yanyang Zhao; Bin Sun; Yanbiao Sun; Jie Wang; Dingxiang Zhuang; Wenjun Li; Lingxue Lu (Carbonates and Evaporites, 2017)

Study the Toxicity to Microcystis aeruginosa Induced by TiO2 Nanoparticles Photocatalysis Under UV Light - Ruirui Lu; Peng Liu; Xiaojuan Chen (Bulletin of Environmental Contamination and Toxicology, 2015)

Genomewide analysis of TCP transcription factor gene family in Malus domestica - RUIRUI XU; PENG SUN; FENGJUAN JIA; LONGTAO LU; YUANYUAN LI; SHIZHONG ZHANG; JINGUANG HUANG (Journal of Genetics, 2014)

Optical and SAR image registration based on improved nonsubsampled wavelet transform for sea islands - Wei Shi; Fenzhen Su; Ruirui Wang; Yongduo Lu (Acta Oceanologica Sinica, 2014)